UPAYA MENANGGULANGI KENAKALAN REMAJA SECARA PREVENTIF, REFRESIF, KURATIF DAN REHABILITASI - Nurotun Mumtahanah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2015)
Reducing juvenile delinquency is so complex because the issues surrounding it are related to one another. This is understandable for the interaction within the community is a system. In regard with very rapid development in any sector of life, the patterns of behavior and lifestyle of teenagers have also changed. The lack of addressing both physical and mental needs could make adolescent psychology become emotionally disturbed and unstabil. The psychological disorder in adolescence and still emotional lability make teenagers misbehave. The form of juvenile delinquency is broadly divided into four, namely individual, situational, systematic and cumulative delinquency. The cause of juvenile delinquency is because of both internal and external factors. Juvenile delinquency can be addressed through preventive, repressive, curative ways, including rehabilitation.